Building The Sets Of Standards For Malaysia Taxi Interior: A Critical Review - Amirul Fahmi, Razali; Addy Putra, Md Zulkifli; Nor Ziratul Aqma, Norzaman (2014)
Taxi has become the most preferable public transportation here in Malaysia. However, the satisfaction from the user, feedbacks was not quite match the real situation. By referring to the several ministers, authorities and prime minister himself, we need to have our own taxi design here in Malaysia, the same thing that had been done by several countries in bringing their own image embedded into their taxis. At the same time, while building the image of the taxi, the other thing is to look into several enhancements towards the user experience. As been stated by the Malaysian previous prime minister and current prime minister themselves, the design taxi should look into the comfort or ergonomics of passengers, the safety issues, some technology appliances and accessibility issue for the disable person1. The main purpose of this study is to first finding an appropriate interior arrangement of the taxi in Malaysia as the sets of standards. The interior design should well answer the criteria stated by the authorities, and the users2. From the interior design, then the image (exterior design) of taxi can only be implemented after the segment of the car had been determined. In order to get the data, the study about what other countries have done must be carried out in order to solve the problems which are actually the same happening here in Malaysia. For the better user experience, several research methods had been conducted in order to get the real user perception towards their experience. The feedback then will be match with the findings from what other countries have done. In filling the gap, taxi used here in Malaysia currently using the existing design of the Proton cars. This is not suitable for the usage as the public transportation5. In this research, the appropriate design or arrangement for the interior of taxi will be determine first before the image of Malaysia can be imbedded into the design of exterior3.